An Investigation into the Factors Influencing the Reduction of Construction Materials Wastage in Erbil City- KRG-Iraq - Khalil Ismail Wali (Zanco Journal of Pure and Applied Sciences, 2020)
The aim of this study is to identify the factors affecting the construction material waste generation and to determine the magnitude of construction waste material in Erbil city. To achieve this study, a form of a questionnaire was prepared comprised of the factors influencing the waste generation of construction material, and assessment of seventeen different construction materials was selected to examine the approximate magnitude of their waste. The survey data was analyzed by adopting the relative important index (RII) method. The result of the analysis revealed that the top significant causes of wastage of materials on construction projects were due to the lack of on-site waste management plans; frequent changes to design, lack of supervision, improper storing of materials; lack of possibilities to order small quantities; lack of skilled workers. Also the study found that the waste percentage of materials used ranged from 3.3% to 8.5%., and the waste percentage of fine aggregate, coarse aggregate, and timber were in a range of 6% to 7% while the waste of cement, steel reinforcement, concrete, concrete block and brick in a range of 5% to 6%, whereas the waste in gypsum reached 8.5%. Furthermore, the study found that poor planning and rework contributing as a significant aspect of waste generation in Erbil city.